Inter-rater reliability of the assessor hazard rating assessment for chemical hazardous to health in Malaysia (Klang Valley) - Adam, Daud (2022)
Competent assessors are trained and developed to cater to the need of industries. This is part of Occupational Safety and Health requirements (Use and Standards of Exposure of Chemicals Hazardous to Health) of Regulation 2000 Part IV assessment of risk to health, Regulation 9. For many types of chemicals used inside any industries, employers are required to commit to a written assessment of the risk due to chemical hazardous to health. The general objective is to determine the inter-rater reliability of chemical health risk assessment hazard rating among competent assessors. Hazard rating determination by competent assessors varies, and this could be due to educational background and experience in the field of chemical assessment and using genuine document of safety data sheet. In this study, a survey using knowledge, attitude and practice concept was conducted on competent assessors registered with Department of Occupational Safety & Health in Selangor and Kuala Lumpur (Klang Valley), and the results found that hazard determination on five different chemicals was not the same. 51% of competent assessors was unsuccessful in getting the accurate hazard rating due to lack of information given on safety data sheet and less effort by assessors to compare to the updated safety data sheet information. Experience-based personnel is an important factor for hazard rating determination. Hazard rating is very important to distinguish which part of the hierarchy control to choose. The result of this study found that the inter-rater professional judgement output is moderately reliable (interclass correlation coefficient value of 0.722) among the assessors since the hazard rating values determined varies. Therefore, academic qualification-based assessor is crucial in providing correct hazard rating value during preparing chemical health risk assessment for occupational safety & health regulatory compliance program